Meningkatkan Percaya Diri Anak Panti Asuhan dalam Penggunaan Bahasa Inggris dengan Metode Groupwork - Sadiah Muayyadah; Bengkel Bengkel (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
In this era of globalization, competition between countries is getting higher, and countries are required to have quality human resources and be able to compete in the global era. The community is expected to have the ability to compete in this competition, and one important ability that must be owned by the community at this time is being able to speak English. In teaching English, there are quite a lot of problems faced by students that become obstacles to the development of their English language skills. One of the problems is a lack of self-confidence. So in this case, the purpose of writing is to increase the confidence of orphanage children in using English so that they understand the basics of the language for everyday life. The location of the fieldwork practice carried out by the author is on Jl. Trumpet No. 88, Titi Chain, Kec. Medan Baru, Medan City, North Sumatra. with the number of children, which on average has gone up. This activity lasted for 3 months. The method used in this practical is the groupwork method by Zastrow. The stages in the groupwork method include (1) engagement, intake, and contract; (2) assessment; (3) planning; (4) intervention; (5) monitoring; (6) evaluation; and (7) termination. The results of these practical activities show an increase in the learning and confidence of the orphanage children in using English. At the beginning of the meeting, the children found it difficult to think of English words. After several meetings, the children started to be more fluent and dared to appear in front of the class to read English sentences, and there was an increase in grades in their school assignments.